Dissecting Inequality-Averse Preferences - Marcelo Bergolo; Gabriel Burdin; Santiago Burone; Mauricio De Rosa; Matias Giaccobasso; Martin Leites (Institute of Labor Economics (IZA), 2021)
Although different approaches and methods have been used to measure inequality aversion, there remains no consensus about its drivers at the individual level. We conducted an experiment on a sample of more than 1800 first-year undergraduate economics and business students in Uruguay to understand why people are inequality averse. We elicited inequality aversion by asking participants to make a sequence of choices between hypothetical societies characterized by varying levels of average income and income inequality. In addition, we use randomized information treatments to prime participants into competing narratives regarding the sources of inequality in society. The main findings are that (1) the prevalence of inequality aversion is high: most participants' choices revealed inequality-averse preferences; (2) the extent of inequality aversion depends on the individual's position in the income distribution; (3) individuals are more likely to accept inequality when it comes from effort rather than luck regardless of their income position; (4) the effect of social mobility on inequality aversion is conditional on individual's income position: preferences for mobility reduces inequality aversion for individuals located at the bottom of the income distribution, where risk aversion cannot play any role.
Keywords: D63; D64; D81; C13; C91; 330; inequality aversion; fairness; risk; effort; luck; redistribution; questionnaire-experiments